KONSELING ISLAMI UNTUK MENGEMBANGKAN KEBERMAKNAAN HIDUP REMAJA DI PANTI ASUHAN - Riem Malini Pane, - (2023)
Riem Malini Pane, 2023 Islamic Counseling to Develop the Meaningful Life of Adolescents at the Hafizil Yatamu (Hayat) Orphanage, Sabungan Jae Village, Padangsidimpuan City, North Sumatra Dissertation. Supervised by: Prof. Dr. Ahman, M.Pd. (Promotor); Prof. Dr. Achmad Juntika Nurihsan, M.Pd. (Co-Promotor). Graduate School of the Indonesian University of Education, Bandung. Every human being has the will to live a meaningful life, and to achieve a meaningful life, in addition to optimizing the individual's potential, he must also receive social support. The reality on the ground shows that many orphanage youths think of themselves as low and withdraw from the crowd. This condition hinders orphanage youth from realizing a meaningful life. The problems of adolescents in orphanages must receive a serious response from various groups so that they can grow normally, both psychologically and psychosocially. The goal of this research is to make a product in the form of Islamic counseling that will help orphanage teens find more meaning in their lives. The Islamic counseling that has come out of this research is based on helping teenagers realize their full potential so that their lives are realistic and full of hope. This study used the Research and Development (R&D) method, which consists of three steps: a preliminary study, development, and testing. The development of Islamic counseling to develop the meaningfulness of the lives of orphanage youth is carried out through groups and individuals. The population in this study were 28 adolescents at Hayat orphanage. Sample withdrawal using purposive sampling technique with a single group design. The research instruments used were observation, interview and questionnaire. To test the effectiveness of Islamic counseling, a comparison of the value of adolescents at the time of the pretest with the posttest value was carried out. The results of this study indicate that as many as 15 out of 28 orphanage adolescents do not realize the meaningfulness of life. The dominant factors that influence the meaningfulness of life of adolescents are family support, social support and gender. Islamic counseling is developed based on 12 formulations, namely: (1) rationale, (2) objectives, (3) assumptions, (4) components, (5) target population, (6) counselor competencies, (7) counselor roles and functions, (8) implementation procedures, (9) stages, (10) counseling mechanisms, (11) activity norms, and (12) evaluation and success indicators. The Islamic counseling that has been prepared is proven to be effective for developing the meaningfulness of life of adolescents in orphanages. Islamic counseling has a positive impact on the meaning of life of adolescents, both in the creative aspect, the experience aspect and the attitude aspect. Keywords: Islamic counseling, meaning of life, adolescents, orphanage